Mastering data warehouse aggregates : solutions for star schema performance - Adamson, Christopher, 1967- (Wiley Pub., 2006)
This is the first book to provide in-depth coverage of star schema aggregates used in dimensional modeling-from selection and design, to loading and usage, to specific tasks and deliverables for implementation projects. It covers the principles of aggregate schema design and the pros and cons of various types of commercial solutions for navigating and building aggregates and discusses how to include aggregates in data warehouse development projects that focus on incremental development, iterative builds, and early data loads--Resource description page.